Developing an Instrument of Performance Assessment to Measure Problem-Solving Skills of Senior High School Students in Physics Inquiry-Based Learning - Alda Novita Sari; Undang Rosidin; Abdurrahman Abdurrahman (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2020)
The assessment of students’ learning results has not been fully implemented. Whereas, the importance of assessing students is to find out the development of learning abilities in solving problems, but many obstacles are still faced by educators at SMAN (high school) 5, SMAN (high school)15, and SMAN (high school) 16 Bandar Lampung. This study aims to produce a valid product and determine the feasibility of construction, substance, and language. Sugiyono's research design development model was divided into (1) potential and problem, (2) data collection, (3) product design, (4) design validation, (5) design revision. The product is valid because the expert validator accepts the instrument in terms of both content and format, including instrument outline, learning scenario, rubric, and scoring guideline. The construction aspect score was 3.59 while the substance aspect score was 3.56, and the language aspect score was 3.58. The validation test result meets very sufficient quality criteria. Therefore, the product performance assessment instrument to measure problem-solving skills in physics inquiry-based learning of senior high school students can be used.